Core-Shell AgPdPt Composite Catalyst Advanced Electrochemical Activity. Issue 2 (9th February 2021) - Tu, Maomao; Shi, Jingling; Ying, Ye; Zheng, YunShan; Wen, Ying; Yang, Haifeng
Abstract : Three kinds of tri-metallic catalysts with core–shell structure are synthesized, in which the outer shell is alloy of Pt and Ag, and the inner core consists of Ag and Pd. Amongst, the composite catalyst with atomic ratio of Ag, Pd and Pt equaling to 1:1.4:1.2 (denoted as Ag1 Pd1.4 Pt1.2 ) has the greatest total mass activity (3310.7 mA mgmetal −1 ), which is much higher than commercial Pt-Ru, Pt- and Pd-based catalysts reported previously. The superior catalytic activity for methanol oxidation should be due to the high amount of Pt alloyed with the least Ag in outer shell and boundary of PtAg outer shell and AgPd inner core composed of tiny nanoclusters, endowing synergistic effect from the electronic structure, numerous defeats, and available great internal and external surface areas. In addition, Ag1 Pd1.4 Pt1.2 catalyst about 250 nm at mesoscopic scale shows improved stability to large extent. Meanwhile, the presence of Pd in Ag1 Pd1.4 Pt1.2 contributes outstanding ability against CO poisoning. This work may pave a promising way to prepare core–shell composite catalyst with high catalytic performance for fuel cell application.